Expectations of Deep Learning Curriculum-Based Learning Review of Government Regulation Number 4 Of 2022 Concerning National Education Standards - Zarkasyi, Ahmad (Yayasan Dinamika Ilmu Banyuwangi, 2025)
This article describes the principles and outcomes of the